Festival repertoire for brass quintet second Bb cornet (trumpet) - SCARLATTI-JOHNSON, A. (Rubank Inc.)
Aria and minuetnBanternCantilenanSourante and RigadoonnFair and WarmernFestival preludenFrom stephen FosternIf thou be nearnMarch regalnPetite concertantenPrelude and badinage